The Multistream Self: Biophysical, Mental, Social, and Existential - Vinod D. Deshmukh (The Scientific World Journal)
Self is difficult to define because of its multiple, constitutive streams of functional existence. A more comprehensive and expanded definition of self is proposed. The standard bio-psycho-social model of psyche is expanded to biophysical-mental-social and existential self. The total human experience is better understood and explained by adding the existential component. Existential refers to lived human experience, which is firmly rooted in reality. Existential living is the capacity to live fully in the present, and respond freely and flexibly to new experience without fear. Four common fears of isolation, insecurity, insignificance, and death can be overcome by developing a lifestyle of whole-hearted engagement in the present reality, creative problem solving, self-actualization, and altruism. Such integrative living creates a sense of presence with self-awareness, understanding, and existential well-being. Well-being is defined as a life of happiness, contentment, low distress, and good health with positive outlook. Self is a complex, integrative process of living organisms. It organizes, coordinates, and integrates energy-information within and around itself, spontaneously, unconsciously, and consciously. Self-process is understood in terms of synergetics, coordination dynamics, and energy-information–directed self-organization. It is dynamic, composite, ever renewing, and enduring. It can be convergent or divergent, and can function as the source or target of its own behavior-mentation. The experience of self is continuously generated by spontaneous activation of neural networks in the cerebral neocortex by the brainstem-diencephalic arousal system. The multiple constitutive behavioral-mental streams develop concurrently into a unique experience of self, specific for a person at his/her developmental stage. The chronological neuro-behavioral-mental development of self is described in detail from embryonic stage to old age. Self can be behaviorally-mentally oriented and realized in three complimentary modes of being: egocentric, allocentric, and ecosystemic or existential. The existential mode is both immanent and transcendent, and can be self-actualized, resulting in a healthy, creative, conflict-free, and meaningful life.